Stimulation of Adenosine 3′:5′-Cyclic Monophosphate Accumulation in Anterior Pituitary Gland In Vitro by Synthetic Luteinizing Hormone-Releasing Hormone - Borgeat, Pierre (1972)
A near-maximal dose (20 ng/ml) of synthetic luteinizing hormone(LH)-releasing hormone/follicle-stimulating hormone(FSH)-releasing hormone added to incubated anterior pituitary tissue of male rats leads to concomitant increases of intracellular concentrations of adenosine 3′:5′-monophosphate and of release of both LH and FSH. The stimulatory effect of LH-releasing hormone/FSH-releasing hormone is observed after a lag period of about 90 min and is progressive at later time intervals; a 3-fold stimulation of cAMP accumulation over control is seen after 210 min of incubation. Half-maximal stimulation of cAMP accumulation is observed between 0.1 and 1.0 ng/ml (0.1-1 nM) of LH-releasing hormone/FSH-releasing hormone. In the presence of 10 mM theophylline, the stimulatory effect of LH-releasing hormone/FSH-releasing hormone on cAMP accumulation is similar to that observed in the absence of the inhibitor of cyclic nucleotide phosphodiesterase, indicating that the releasing hormone exerts its effect by specific activation of adenylate cyclase in LH- and FSH-secreting cells rather than by inhibition of cyclic nucleotide phosphodiesterase. Since the release of growth hormone, thyrotropin, prolactin, and adrenocorticotropic hormone is not affected by LH-releasing hormone/FSH-releasing hormone, and since cAMP stimulates the release of all six adenohypophyseal hormones. the observed changes of cAMP concentrations indicate specific stimulation of adenylate cyclase activity in LH-and FSH-secreting cells of the adenohypophysis.